Cognitive activities and cognitive performance in middle-aged adults at risk for Alzheimer’s disease - Jonaitis, Erin (2013)
Cognitive activity is thought to provide some protection against dementia, but the mechanism and timing of these effects are unknown. Data for this study were drawn from the Wisconsin Registry for Alzheimer’s Prevention (WRAP), an at-risk middle-aged sample (mean age = 54 years) enriched for parental family history of Alzheimer’s disease (AD). We had two main aims: (1) to determine the relative contribution of three facets of cognitive activity -- education, occupational complexity with data, and cognitive leisure activities – to WRAP participants’ cognitive performance; and (2) to assess for interactions between genetic risk factors and cognitive activity in explaining cognitive performance. Results from mixed effects models indicate that some of the variance usually attributed to education may be more closely accounted for by cognitive activities later in life. Overall, our analyses suggest cautious optimism for cognitive activities, especially game-playing, as a strategy for preserving cognitive strengths in midlife.